Heterogeneous catalysis : fundamentals and applications - Ross, J. R. H. (Amsterdam : Elsevier, 2012)
'Heterogeneous catalysis plays a part in the production of more than 80% of all chemical products. It is therefore essential that all chemists and chemical engineers have an understanding of the fundamental principles as well as the applications of heterogeneous catalysts. This book introduces the subject, starting at a basic level, and includes sections on adsorption and surface science, catalytic kinetics, experimental methods for preparing and studying heterogeneous catalysts, as well as some aspects of the design of industrial catalytic reactors. It ends with a chapter that covers a range of examples of important catalytic processes. The book leads the student to carrying out a series of'tasks' based on searches of the internet and also on the use of web-based search tools such as Scopus or Web of Science. These tasks are generally based on the text; they can be used entirely for self-study but they can also be tailored to the requirements of a particular course by the instructor/lecturer giving the course.'--P. [4] of cover.
Surfaces and Adsorption -- What is a Catalyst? -- The Catalytic Reactor -- Kinetics of Catalytic Reactions -- Mechanisms of Catalytic Reactions -- Transport Processes within the Catalyst Particle -- Important Industrial Processes.
Includes bibliographical references and index.
Keywords: Heterogeneous catalysis